Health expenditures and economic growth: A literature review - Chaarouk, Otmane (2025)
The creation of economic wealth is a central goal of the modern capitalist system, and various means can be explored to stimulate this creation. Due to the significant correlation between population health and economic performance, health is increasingly recognized as a catalyst for growth, especially after the Covid-19 pandemic. Health expenditures, in particular, can play a key role in determining health outcomes and, by extension, contribute to economic growth. Therefore, this literature review focuses on the impact of health expenditures on economic growth, examining existing research to provide a basis for future studies.